Branding Desa Paseseh sebagai Desa Eduwisata Melalui Pengembangan Web dan Galeri Batik sebagai Pusat Informasi Online dan Offline - Ernaning Widiaswanti; Retno Indriartiningtias; Arik Kurniawati; Ahmad Jauhari (Jurnal Pengabdian Masyarakat Charitas, 2025)
This community service activity is part of the Bima Program Community Service Grant in the form of KKNT organized by DIKTI. This KKNT was held in Paseseh Village, Tanjungbumi, Bangkalan, Madura. There are several objectives and outcomes to be achieved in this KKNT, but this article focuses on the main issue related to branding Paseseh Village as a Batik Educational Tourism Village. Branding is carried out by designing a website and improving the mini batik gallery, which functions not only as a marketing center for batik products, but also as an information center for everything related to batik, information about Paseseh Village, and the tourism potential there. With this online and offline branding, it is hoped that more Indonesians will recognize Paseseh Village as an Educational Tourism Village.